Comparative analysis of the inheritance of a high development rate in the Rimax and Rico lines of spring bread wheat (Triticum aestivum L.) - B. V. Rigin; Е. V. Zuev; А. S. Andreeva; I. I. Matvienko; Z. S. Pyzhenkova (Труды по прикладной ботанике, генетике и селекции)
Background. Development of early-ripening spring bread wheat (Triticum aestivum L.) cultivars is an important task for Russian breeders. Knowledge of the genetics of ultraearly varieties – sources of valuable genes that determine an earlier-maturing type of plant development –will be used to work out methods for obtaining source material for breeding.Materials and methods. The ultra-early lines Rico (k-65588, var. erythrospermum Koern.) and Rimax (k-67257, var. lutescens (Alef.) Mansf.), and cvs. ‘Max’ (k-57181, var. lutescens) and ‘Leningradskaya 6’ (k-64900, var. lutescens) were studied. Alleles of the Vrn and Ppd genes were identified by PCR according to known publications, and genomic DNA was isolated from 3-day-old seedlings by the CTAB method.Results. In the environments of Northwest Russia, the Rimax and Rico lines are characterized by the highest rate of development before heading among the spring wheat accessions from the VIR collection. In the Rimax and Rico genotypes, the Vrn-A1, Vrn-B1, Vrn-D1 and Ppd-D1 genes were found. Genotypes with different alleles of Ppd-D1 and Vrn-B1 were identified in the Rimax line. Under conditions of a long day (18 hours), in the population of F2  (F3) Rico × Rimax hybrids, the ratio of phenotypes with a high development rate to all others was observed as 1 : 15 (χ2 1: 15 = 0.64). Under a short day (12 hours), 5 clearly tested groups were identified in F2 with the ratio 1 : 4 : 6 : 4 : 1 (χ2  = 3.03; χ2 0.05 = 9.48), which indicates the manifestation of cumulative polymerization.Conclusion. Each of the Rimax and Rico lines has two pairs of independent duplicated genes that determine a high development rate. Under short-day conditions, these genes can interact like cumulative polymers. The Rimax and Rico lines, due to their high development rate, are valuable source material to be used in breeding for earliness.